Peran dan fungsi prostesis dalam fungsi sistem stomatognatik Role and function of prosthesis in the stomatognathics system function - Muslich Mahmud; Jeffrey Jeffrey (DiscoverSys Inc., 2012)
Do literary study of the role and function of the prosthesis in overcoming or restoring function stomatognathicsystem cannot function optimally. There is a variety of lost body parts due to illness or accident requiringabnormalities restoration or rehabilitation with artificial materials. To overcome this thing, there are a variety ofprosthesis, the dental prosthesis, maxillofacial prosthesis, and supporting prosthesis (ancillary prosthesis). Theanalysis focused on overcoming tooth loss causes shortening jaw arch and various maxillofacial abnormalitiesusing compatible materials, a variety of complications and their consequences. Data showed that the loss of thesystem's structure can disrupt stomatognathic masticatory function, esthetics, phonetics, swallowing and breathing.Installation of a removable prosthesis, partial or full will improve the efficiency of mastication and chewing ability,a greater increase in fixed prostheses and implants. Esthetic and satisfaction very disturbed due to missing fronttooth with a large variation of subjectivity for the age group, social, cultural, regional and state. Generally, patientsare less affected by the phonetic compared to mastication. Although not fully, function prosthesis can replacemissing teeth and the surrounding tissue, and keep tissue health of the stomatognathic system. It was concluded thatprosthesis can help, restore and maintain function of stomatognathic system, namely the mastication, esthetics,phonetics, swallowing and breathing.